Educação patrimonial: novos rumos da conscientização acerca do patrimônio vivo por meio da terapia ocupacional - Silva, Mircele Massirer Rodrigues Da (2019)
A brief historical review, from the history of madness to the revolutionary achievements of the renowned psychiatrist Dr. Nise da Silveira in the 20th century, in the field of mental health, art and culture, comes the reflection proposed by this study, which is the humanization of care to users of mental health services. This research noticed that there are still different modes of treatment and thinking, in some respects, indifferent to "Niserian" methods, although the advent of psychiatric reform in 2001 advocating more humanized care in mental health. Considering that, various possibilities of working with art and culture were implemented by Dr. Nise da Silveira in occupational therapy workshops and have always been very close to the definitions of what is cultural heritage in its material and immaterial aspects. General objective: To think over the living heritage, regarding the work developed in expressive workshops in occupational therapy with users in mental health services. Specific objective: To promote the awareness of occupational therapists and other mental health workers to the importance of valuing the memory and identity contained in the users' productions. Method: The investigative course of this research was based on the use of the Research-Action-Participant method that according to Thiollent (2005, p.16) "Is a type of social research that is carried out from the desire to solve collective problems, in which the researcher and the participants are involved in the reality to be investigated.” Results: Elaboration of an adapted booklet based on Education on Cultural Heritage methodology. It was carried out in five stages to be used by occupational therapists as an instrument to facilitate the transition of the user's occupational roles in mental health, convoking occupational therapists to mediate the users to leave the condition of "crazy", going towards to be recognized as "alive patrimony". Final considerations: it was understood that the knowledge about mental health and cultural heritage in an interdisciplinary relationship with other fields does not end with this research, but only begins. There is still much to be done to benefit the quality of life of the human being, based on the appreciation of the cultural heritage created by him, even in a "differentiated state of being".